Hubungan rasio P(v-a)CO2/C(a-v)O2 terhadap lactate clearance sebagai penanda keberhasilan One Hour Bundle pada pasien sepsis: Pendekatan metode statistik regresi - Taufik, Maulana; Nadeak, Rommy Fransiscus; Irina, Rr. Sinta; Wahyuni, Arlinda Sari (Poltekkes Kemenkes Aceh, 2025)
Background: A prognostic predictive value in patients with sepsis and septic shock is needed to determine the aggressiveness of the therapy we will choose. Various methods are used to predict patient mortality. Based on this, a marker is needed to assess tissue perfusion disorders.Objectives: To determine the relationship between the P(v-a)CO2/C(a-v)O2 ratio and lactate clearance as a marker of the success of the one-hour bundle in sepsis patients.Methods: This study is a descriptive analytic study of 40 patients who assessed the description of lactate, ScvO2, and PvaCO2 gap values in septic patients. The study was conducted at the Emergency Department (IGD) and Intensive Care Unit (ICU) of H. Adam Malik Hospital Medan, during the period of April to May 2023. The collected data were then analyzed using descriptive statistical methods to calculate the mean, standard deviation, and range of the variables studied. The differences between groups were analyzed using the t-test to compare the mean values of the parameters studied. Correlation analysis was conducted using Pearson’s correlation test to assess the relationship between lactate, ScvO2, and PvaCO2 gap.Results: At T0, the mean lactate level was 22,06 mmol/L (median 16,85 mmol/L), the mean P(v-a)CO2 was 9,28 mmHg (median 8,50 mmHg), and the mean P(v-a)CO2/C(a-v)O2 ratio was 3,66 (median 3,56). At T1, the mean lactate level decreased to 12,52 mmol/L (median 9,00 mmol/L), the mean P(v-a)CO2 was 8,50 mmHg (median 7,50 mmHg), and the mean P(v-a)CO2/C(a-v)O2 ratio was 3,45 (median 2,57). The average lactate clearance was 48,29%. Bivariate analysis revealed a significant relationship between lactate clearance and the P(v-a)CO2/C(a-v)O2 ratio, with a P-value of 0,009 and a Spearman correlation of -0,521, indicating a strong negative correlation between the two variables.Conclusion: There is a significant relationship between the P(v-a)CO2/C(a-v)O2 ratio and lactate clearance in the success of the one-hour bundle for sepsis patients.